Optimal current setpoint computation for externally excited synchronous machines - Reinhard, Johannes; Lohe, Klaus; Graichen, Knut (Control Technology and Applications (Online), 2022)
Torque control strategies for externally excited synchronous machines are typically based on calculating suitable reference currents, whereby system limitations such as the maximum possible phase and excitation current as well as the maximum voltage of the inverters must be taken into account. Based on the static voltage equations of the dq-model, a nonlinear constrained optimization problem is derived in this paper, which aims at minimizing copper losses and finding the optimal reference currents for a desired torque subject to the aforementioned constraints. This problem is then solved by a combinatorial algorithm which allows the solution to be computed efficiently in real time. Simulations and a comparison with an approach from the literature show the suitability of the algorithm with respect to the quality of the achieved torque and loss minimization as well as the low computational load.